Learning from experience: shared constructs in virtual reality and occupational therapy. - Foran, Amanda C. (International Journal of Therapy & Rehabilitation, 2011)
Background: Rehabilitation professionals have long accepted the belief that engagement in meaningful activity contributes to human development and can enhance health and wellbeing. More recently, theorists have begun to discuss the importance not only of engagement in such activities, but the experience one has while engaging in them. With this shift, it is important for scholars of rehabilitation, in particular occupational therapy theorists and clinicians, to develop better ways to describe and measure occupational experience. Contents: This article considers how an understanding of occupational experience can be enhanced by taking up constructs in virtual reality theory that are similar to those in occupational therapy and occupational science, such as immersion, presence, flow, and embodiment. Correspondingly, the growing field of virtual reality can benefit from occupational therapists' and occupational scientists' work on occupational presence, therapeutic occupation, and the adaptation of contexts (including virtual contexts) to fit individual needs. Conclusions: As both virtual reality and occupational therapy continue to evolve, it is critical that scholars in each field look outside current paradigms to seek knowledge that is mutually beneficial to advancing understandings of human experience.